VISUAL REPRESENTATION OF HEDONISM IN ‘PARASITE FILM’ - Adinda Maharani; Acep Iwan Saidi (Universitas Negeri Makassar, 2021)
Parasite is one of the films that have a message that shows signs in every scene in class domination. This study aims to analyze the Parasite film by looking at the visual presentation aspect associated with the hedonism perspective carried out by Kim Ki-taek's family figure who comes from the lower class. The research method used is a qualitative approach with a descriptive method that uses Roland Barthes' semiotic analysis. The results of the study show that Parasite is a realistic dark comedy thriller movie. This Parasite movie makes spectral arrogance have a strong emotional effect on one of the film's characters and it turns out that it has no basis in the metaphysical realm but in the economic realm in the form of the emergence of hedonism in Kim Ki-taek's family character. The depiction of two different conditions between the Park Dong-ik family and the Kim Ki-taek family, which in reality describes the two different worlds in which the poor and the rich life.